Mobile augmented reality learning objects in higher education - Faith Marcel (Association for Learning Technology, 2019)
Teachers and learners in all sectors of education continue to have access to a growing number of mobile augmented reality (AR) applications for the creation and implementation of mobile AR experiences and learning objects (LOs). In this study, affordances of mobile AR and LOs for higher education are investigated through the mobile AR platform HP Reveal. Digital trace data from publicly shared and published AR users' LOs were examined to investigate affordances of AR technology in educational organisations and institutions and their potential implications in areas of higher education. For this purpose, a quantitative comparative analysis of system data and content from 632 AR LOs was conducted at two instances over a 2-year interval period. Each LO was thematically coded to determine multimodal functionalities and characteristics. Further thematic coding and categorisation revealed four emergent categories for affordances in higher education: learner interaction, collaboration, cultural exploration and digital storytelling. Results also revealed increases over time in the use of recorded and online video content and the use of three-dimensional (3D) characters for educational purposes. An examination of the affordances offered by the AR platform revealed opportunities for educators to explore further interactive and collaborative uses of AR with their learners for pedagogical purposes in higher education.